Social theory and narrative research: a point of view. Issue 1 (2nd January 2016) - Denison, Jim
Abstract : In this short essay, I explore in a narrative style the following question: do narrative analyses of sport and exercise need to engage more fully with social theory in order to become more forceful in their arguments? More specifically, to have real impact, and to achieve what we are especially trained to do as qualitative social scientists, should our research narratives examine more explicitly—less showing and more telling—the complex relations of power that circulate in and around our topics? It is my aim in this commentary to stake out a position for narrative research that goes beyond modernist representational traditions in order to problematize our understanding of ourselves and others as active moving bodies.